The Clique : A Novel - Harrison, Lisi (London Simon and Schuster, 2007)
Clueless with Claws. Enter the world of the Clique - where the only thing harder than getting in is staying in...
Keywords: Cliques (Sociology) -- Social Classes -- Middle Schools